Modelagem da expansão urbana futura como suporte ao planejamento e ao ordenamento territorial para a cidade João Pessoa – PB - Rocha, Paula Isabella de Oliveira (2023)
This research aims to analyze urban growth from the 1990s onwards and estimate future expansion scenarios for the years 2030, 2035 and 2040, in the municipality of João Pessoa-PB. The methodology was carried out in two stages. The first stage consisted of analyzing changes in urban expansion based on the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-up Index (NDBI), processed on the Google Earth Engine platform. To calculate these two indices, images from the Landsat 5, 7 and 8 satellites from the years 1990, 1992, 2000, 2001, 2006, 2010 and 2016, available on the USGS GloVis platform, were used. The second stage consisted of the classification of land use and land cover of the city, and the modeling of future urban expansion using the Land Change Modeler (LCM) software. For this stage, three of the most recent images were chosen (2001 (t1), 2006 (t2) and 2018 (t3)). The classification of land use and land cover was carried out using the supervised method of maximum likelihood. Images from years t1 and t2 were used to identify patterns of land cover change, and thus generate the transition potential between these covers. Then, the land cover was estimated in the period t3, followed by the validation and calibration of the model produced. After this step, it was possible to estimate the land use and land cover in the municipality of João Pessoa for the years 2030, 2035 and 2040. The results pointed to an increase of 445% in the built-up area between the years 1990 and 2016. Also, it was observed that the plots of area indicative of vegetation, both those with medium and high vegetative vigor, suffered a decrease, indicating environmental degradation to the detriment of urban growth. The comparison between the identified urban growth and the municipality's macrozoning law indicated satisfactory effectiveness of the urban planning instruments. It can be concluded that the process of modeling future scenarios presented two trends: (a) the first trend considered greater transition potential in bordering areas between one land cover class and another, concentrating growth close to the urban center, disregarding the emergence of urban agglomerations in more peripheral areas, and (b) the second trend revealed faster urban growth than actually occurred, resulting in the depletion of areas of vegetation that could be transitioned before the year 2040.